FMRFamide-Related Peptides Signaling Is Involved in the Regulation of Muscle Contractions in Two Tenebrionid Beetles - Marciniak, Paweł; Witek, Wojciech; Szymczak, Monika; Pacholska-Bogalska, Joanna; Chowański, Szymon; Kuczer, Mariola; Rosiński, Grzegorz (Frontiers in Physiology, 2020)
Peptidergic signaling regulates various physiological processes in insects. Neuropeptides are important messenger molecules that act as neurotransmitters, neuromodulators or hormones. One of the group of neuropeptides with myotropic properties in insects is known as FMRFamide-related peptides (FaRPs). Here, we describe the myotropic effects of the endogenous FMRFamide related peptide (NSNFLRFa) in the regulation of contractile activity of the heart, ejaculatory duct, oviduct and the hindgut in two beetle species, Tenebrio molitor and Zophobas atratus. A putative receptor was identified in silico in both species. Using RT-PCR technique, receptor was found in the various tissues of both beetles, including visceral organs. Analysis of the amino acid sequence of the receptor indicated that it is similar to other insect FMRF-amide receptors and belongs to G-protein coupled receptors. The tested peptide showed concentration-dependent and organ-specific myoactive properties. It showed species–specific cardioactivity, in that it stimulated Z. atratus heart contractions, while slightly inhibiting that of T. molitor and had mainly myostimulatory effect on the examined visceral organs of both beetle species,with the lowest activity in the ejaculatory duct of these beetles. The peptide was the most active in the hindgut of both species, but only at high concentration of 10-5 M. The results suggest that FMRFamide-related peptides are potent modulators of endogenous contractile activity of the visceral muscles in beetles and may indirectly affect various physiological processes.